Case report: Rare intrapulmonary malignant mesothelioma complicated with myositis - Gong, Dandan; Yu, Jian; Jiang, Xiaodong (Frontiers in Oncology, 2022)
Malignant pleural mesothelioma is an uncommon aggressive tumor. Its incidence is even lower when the lung parenchyma is the primary site. Myositis is a common paraneoplastic syndrome, but it rarely presents with malignant pleural mesothelioma. This report presents a rare intrapulmonary malignant mesothelioma complicated by cancer-associated myositis. The patient presented with limb muscle weakness as the first symptom and was diagnosed with intrapulmonary malignant mesothelioma complicated by cancer-associated myositis on the basis of clinical, histological, immunohistochemical, and radiological findings. The patient responded poorly to conventional hormone therapy and died of respiratory failure within 2 months after the first presence of limb muscle weakness.